2016
DOI: 10.1371/journal.pone.0151151
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Spatio-Temporal Variability in the Reproduction Ratio of the Bluetongue (BTV-1) Epidemic in Southern Spain (Andalusia) in 2007 Using Epidemic Trees

Abstract: Andalusia (Southern Spain) is considered one of the main routes of introduction of bluetongue virus (BTV) into Europe, evidenced by a devastating epidemic caused by BTV-1 in 2007. Understanding the pattern and the drivers of BTV-1 spread in Andalusia is critical for effective detection and control of future epidemics. A long-standing metric for quantifying the behaviour of infectious diseases is the case-reproduction ratio (Rt), defined as the average number of secondary cases arising from a single infected ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
4
15
0
Order By: Relevance
“…Consistent with this hypothesis, the re-emergence of the virus in France in 2015 occurred in a cattle production region and only involved a few cases in sheep [ 14 ]. Results revealing a considerable role played by sheep are, however, also congruent with a recent work that showed that BTV-1 transmission increased significantly in areas with higher densities of sheep during the epidemic of 2007 in southern Spain [ 55 ]. Our results also supported a positive association of BTV spread with the density of goats, which rarely display clinical signs and are generally not considered to play an important role in BTV transmission [ 56 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with this hypothesis, the re-emergence of the virus in France in 2015 occurred in a cattle production region and only involved a few cases in sheep [ 14 ]. Results revealing a considerable role played by sheep are, however, also congruent with a recent work that showed that BTV-1 transmission increased significantly in areas with higher densities of sheep during the epidemic of 2007 in southern Spain [ 55 ]. Our results also supported a positive association of BTV spread with the density of goats, which rarely display clinical signs and are generally not considered to play an important role in BTV transmission [ 56 ].…”
Section: Discussionsupporting
confidence: 88%
“…BTV transmission is optimal at a mean temperature of 20°C–25°C and decreases at both warmer and cooler temperatures [ 21 , 60 ]. During a 2007 outbreak of BTV-1 in Andalusia for example, there was an overall positive correlation between temperature and basic reproductive number (R0); however, it has been shown that this relationship was not linear [ 55 ]. Given these complexities, it might be more appropriate to consider temperature in a nonlinear fashion by examining critical thresholds and classifying resistance values accordingly [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Napp et al. () estimated the case‐reproduction ratio (R t ) for the BTV‐1 spread in Andalusia in 2007, resulting in values ranging from 4.6 in July, to 2.2 in August, and below 1 in September (0.8) and October (0.02).…”
Section: Assessmentmentioning
confidence: 99%
“…Obviously, the speed of transmission is strongly influenced by the vector abundance and, therefore, by the local climatic conditions. Napp et al (2016) estimated the case-reproduction ratio (R t ) for the BTV-1 spread in Andalusia in 2007, resulting in values ranging from 4.6 in July, to 2.2 in August, and below 1 in September (0.8) and October (0.02).…”
Section: Speed Of Transmissionmentioning
confidence: 99%
“…To externally assess the performance and usefulness of the monthly transmission risk maps we used historical data from 2007–2018 of BTV-1 (11,482) and BTV-4 (506) outbreaks from the European Animal Disease Notification System (ADNS) database [ 97 ], excluding BTV outbreaks in wildlife. We used an estimation of 14 day-lapse between the day of infection and the date of suspicion [ 98 ]. The suspicion date was calculated when missing from the mean lapse time between the suspicion and confirmation dates from observations with data (approximately 20 days).…”
Section: Methodsmentioning
confidence: 99%